Rabia Akhtar, The Blind Eye: US Non-Proliferation Policy Towards Pakistan from Ford to Clinton - Saima Aman Sial (CISS Insight Journal, 2018)
The subject of Pak-US relations is an area where the literature is mostly burdened with conflicting narratives on both sides rather than a matter of fact analysis of historical events. Rabia Akhtar’s book, The Blind Eye: US Nonproliferation Policy Towards Pakistan from Ford to Clinton makes an attempt to set the record straight. This book is a timely addition to the literature which provides a new prism to look at Pakistan’s pursuit of the bomb during times of changing US nonproliferation goalposts. In its critique on the US non-proliferation policies, the book concludes that Pakistan’s popular narrative needs a reset with respect to the objectives and successes of the US non-proliferation policies towards Pakistan.